Face Recognition and Emotions in Education: Unlocking the Potential of Face Analysis Technology - Tokhirjonova Muattarkhоn Rasuljon kizi (European Science Publishing, 2023)
This article explores the transformative potential of face recognition and emotions analysis technology in education. With advancements in artificial intelligence (AI), face analysis technology has emerged as a powerful tool for understanding and interpreting facial expressions, enabling educators to unlock valuable insights into students' emotional states during the learning process. This article delves into various applications of face recognition and emotions analysis in education, including student engagement monitoring, personalized instruction, and mental well-being support. It examines the benefits and challenges associated with the integration of this technology and addresses ethical considerations in the educational context. By harnessing the power of face analysis technology, educators can gain a deeper understanding of students' emotional responses, create more engaging learning environments, and provide targeted support to enhance learning outcomes and overall well-being.
Keywords: artificial intelligence, learning process, virtual assistant, adaptive learning.